Fertilizantes nitrogenados de eficiência aumentada e convencionais na cultura do cafeeiro - Dominghetti, Anderson William (2016)
With this study, we aimed at evaluating the influence of the use of different nitrogen fertilizers regarding nitrogen (N) loss by ammonia volatilization; emission of carbon dioxide (CO 2); foliar content of N, S, Cu and B; soil pH; productivity and coffee production cost. The experiment was conducted in an experimental field at the Universidade Federal de Lavras, Lavras, Minas Gerais, Brazil, using a randomized blocks design with three replicates, during two years (from August 2013 to July 2015). The treatments consisted of ten nitrogen fertilizers: urea, ammonium sulfate, urea dissolved in water, ammonium nitrate, urea + copper (Cu) + boron (B), urea + anionic polymer, urea + sulfur (S) + polymer, urea + thermoplastic resin, urea + NBPT, and urea formaldehyde, in a total equivalent to 450 kg ha -1 of N, divided into three applications at intervals of sixty days. During the first year, the average nitrogen loss by volatilization followed the decreasing order: urea + anionic polymer (35.8%) > urea (31.2%) = urea + S + polymer (30.9%) > urea + Cu + B (25.6%) > urea + NBPT (11.9%) = urea + resin (8.6%) > urea dissolved in water (4.6%) = urea formaldehyde (1.1%) = ammonium sulfate (0.9%) = ammonium nitrate (0.3%). For pH values and foliar N, we verified decrease wit h the progression of the evaluations. However, there was no significant difference of the final mean between treatments, as well as for the foliar contents of S, Cu and B. Regarding CO 2 emission, there was variation between all three fertilizations, motiva ted especially by edaphoclimatic factors in the area. In average, we verified higher emission of urea, urea + anionic polymer, urea + Cu + B, urea + S + polymer and urea + resin. During the second year, in the mean of the three fertilizations, the decreasing order of the amount of volatilized N was: urea + anionic polymer (41%) = urea (38%) > urea + S + polymer (29%) urea + NBPT (26%) > urea + Cu + B (17%) = urea + resin (16%) > urea dissolved in water (5%) = ammonium sulfate (1%) = urea formaldehyde (1%) = ammonium nitrate (0.2%). The lowest pH values were obtained with the use of ammonium nitrate, ammonium sulfate and urea formaldehyde, regarding this year, and the foliar contents of N were not influenced by higher losses in some of the fertilizers. In addition, there was no difference between the sources regarding the foliar contents of Cu. The foliar contents of S were higher with the use of ammonium sulfate. There was no significant difference between productivity means of 2015/2016. The use of urea + Cu + B provided lower total operational cost per hectare, fertilizer Urea + resin, the highest cost, and urea + NBPT, the higher net margin.